Effect of Bilastine on Diabetic Nephropathy in DBA2/J Mice - Roberta Verta (International Journal of Molecular Sciences, 2019)
Diabetic nephropathy is an unmet therapeutic need, and the search for new therapeutic strategies is warranted. Previous data point to histamine H1 receptor as a possible target for glomerular dysfunction associated with long term hyperglycaemia. Therefore, this study investigated the effects of the H1 receptor antagonist bilastine on renal morphology and function in a murine model of streptozotocin-induced diabetes. Diabetes was induced in DBA2/J male mice and, from diabetes onset (glycaemia ≥200 mg/dL), mice received bilastine (1−30 mg/kg/day) by oral gavage for 14 consecutive weeks. At the end of the experimental protocol, diabetic mice showed polyuria (+195.5%), increase in Albumin-to-Creatine Ratio (ACR, +284.7%), and a significant drop in creatinine clearance (p < 0.05). Bilastine prevented ACR increase and restored creatinine clearance in a dose-dependent manner, suggesting a positive effect on glomerular filtration. The ultrastructural analysis showed a preserved junctional integrity. Preservation of the basal nephrin, P-cadherin, and synaptopodin expression could explain this effect. In conclusion, the H1 receptor could contribute to the glomerular damage occurring in diabetic nephropathy. Bilastine preserved the glomerular junctional integrity, leading to the hypothesis of anti-H1 antihistamines as a possible add-on therapy for diabetic nephropathy.